Mathematical Model To Identify Heavy Metal In Irrigation Channel From Cicabe Final Disposal Site - Elsa Try Julita Sembiring; Idris Maxdoni Kamil (Universitas Trisakti, 2018)
Aim: This study has been done to investigate the contamination in the main open channel using mathematical modeling to describe the pollutant transport of groundwater around the Cicabe final disposal site, Mandalajati Village, Bandung (coordinate 6°53'50